Pemberdayaan Keluarga melalui Sekolah Parenting: Upaya Mengurangi Ketergantungan Gawai pada Anak - Fitri Pertiwi; Herlina Siregar (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Children's dependence on digital devices has become a serious issue affecting their cognitive, social, emotional, and physical development. Low levels of digital parenting literacy within families further worsen the situation, necessitating interventions focused on empowering parents through systematic educational approaches. The community service activity aimed to enhance families' capacity to manage healthy device use through a Parenting School program implemented in Kampung Bojong Neros. The method employed was a participatory approach consisting of preparation, implementation, evaluation, and follow-up stages. The program involved 15 families (15 parents and 15 school-aged children) conducted over three consecutive days through educational sessions and collaborative family practices. Quantitative evaluation revealed a significant increase in parents' understanding scores from 48% to 82%, while children's scores increased from 55% to 97%. Beyond knowledge improvement, positive behavioral changes were identified, including implementation of device-use rules at home, increased digital discipline, and greater interest among children in more constructive alternative activities. The parenting school proved effective in strengthening digital parenting literacy and reducing device dependency through active family engagement. The program offers opportunities for broader development through continued mentoring and strengthened community networks to ensure impact sustainability.